2019
DOI: 10.3329/jbas.v43i1.42230
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Salinity on the Growth and Development of Groundnut PlANT (Arachis hypogaea L.)

Abstract: The present study investigated the effects of salinity on the growth of groundnut (Arachis hypogaea L.), variety BARI Badam-8. The plants were grown in a series of plastic pots under controlled light and temperature conditions in the growth room. Salt (NaCl) solutions of different concentrations (0 mM, 50 mM, 100 mM, 150 mM, 200 mM, and 250 mM) were added to the pots, with three replicates. Results showed that shoot height, number of plants, main root length and lateral root length significantly decreased with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 4 publications
1
0
0
Order By: Relevance
“…Severe salinity may inhibit shoot and plant growth due to slow uptake of water by the plant which might be another cause for this decrease (Werner and Finkelstein 1995). These results also consist with Satu and Ahmad (2019) who reported that shoot fresh weight of groundnut abated with increasing salinity level, where salinity reduced shoot fresh weight of groundnut.…”
Section: Root Dry Weight (G)supporting
confidence: 80%
“…Severe salinity may inhibit shoot and plant growth due to slow uptake of water by the plant which might be another cause for this decrease (Werner and Finkelstein 1995). These results also consist with Satu and Ahmad (2019) who reported that shoot fresh weight of groundnut abated with increasing salinity level, where salinity reduced shoot fresh weight of groundnut.…”
Section: Root Dry Weight (G)supporting
confidence: 80%